53.8k views
0 votes
Prove by mathematical induction the following statement:

n.1 + (n-1).2+ (n-2).3+...+2(n-1)+1.n= 1/6n(n+1)(n+2)
Please I really really need help with this. I've tried and tried to no avail. Thanks in advance. Thank you.

User Xyzzyrz
by
5.4k points

1 Answer

2 votes

Answer:

In Exercises 1-15 use mathematical induction to establish the formula for n ≥ 1.

1. 1

2 + 22 + 32 + · · · + n

2 =

n(n + 1)(2n + 1)

6

Proof:

For n = 1, the statement reduces to 12 =

1 · 2 · 3

6

and is obviously true.

Assuming the statement is true for n = k:

1

2 + 22 + 32 + · · · + k

2 =

k(k + 1)(2k + 1)

6

, (1)

we will prove that the statement must be true for n = k + 1:

1

2 + 22 + 32 + · · · + (k + 1)2 =

(k + 1)(k + 2)(2k + 3)

6

. (2)

The left-hand side of (2) can be written as

1

2 + 22 + 32 + · · · + k

2 + (k + 1)2

.

In view of (1), this simplifies to:

User Joshpt
by
5.2k points